Perimenstrual Asthma in Adolescents: A Shared Condition in Pediatric and Gynecological Endocrinology - Valeria Calcaterra; Rossella Elena Nappi; Andrea Farolfi; Lara Tiranini; Virginia Rossi; Corrado Regalbuto; Gianvincenzo Zuccotti (MDPI AG, 2022)
Asthma is a frequent medical condition in adolescence. The worsening of the most common symptoms perimenstrually is defined as perimenstrual asthma (PMA). The cause of PMA remains unclear, but a role for hormonal milieu is plausible. Data on PMA in adolescents are limited, and its management is not fully established. We aimed to discuss the PMA phenomenon in young females from pathophysiology to preventive strategies, focusing on the relationship with the hormonal pattern. The fluctuation of estrogens at ovulation and before menstruation and the progesterone secretion during the luteal phase and its subsequent withdrawal seem to be the culprits, because the deterioration of asthma is cyclical during the luteal phase and/or during the first days of the menstrual cycle. Conventional asthma therapies are not always effective for PMA. Preventive strategies may include innovative hormonal contraception. Even a possible beneficial effect of other hormonal treatments, including estrogens, progestogens, and androgens, as well as leukotriene receptor antagonists and explorative approach using microbial-directed therapy, is considered. The underlying mechanisms, through which sex-hormone fluctuations influence asthma symptoms, represent a challenge in the clinical management of such a distressing condition. Further studies focused on young females are mandatory to promote adolescent health.